The impact of retrotransposons on castor bean genomes - Kong, Lin; Zhang, Tingting; Ma, Lei (Frontiers in Plant Science, 2024)
Castor bean (Ricinus communis L.) is an important oil crop. However, the influence of transposable elements (TEs) on the dynamics of castor bean evolution awaits further investigation. This study explored the role of transposable elements in the genomes of wild castor bean accessions from Ethiopia (Rc039) and Kenya (WT05), as well as in the cultivated variety (Hale). The distribution and composition of repeat sequences in these three lineages exhibited relative consistency, collectively accounting for an average of 36.7% of the genomic sequences. Most TE families displayed consistent lengths and compositions across these lineages. The dynamics of TEs significantly differed from those of genes, showing a lower correlation between the two. Additionally, the distribution of TEs on chromosomes showed an inverse trend compared to genes.Furthermore, Hale may have originated from the ancestor of Rc039. The divergent evolutionary paths of TEs compared to genes indicate the crucial role of TEs in shaping castor bean genetics and evolution, providing insights for the fields of castor bean and plant genomics research.